PENGARUH LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN DAN NET INTEREST MARGIN TERHADAP PROFITABILITAS - Supriyatna, Kadek Dwi; Candradewi, Made Reina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p18, 2023)
Bank Pembangunan Daerah (BPD) are a group of financial institutions that play a role in driving the regional economy by supporting development financing in the regions. PT. BPD must be able to increase efficiency in carrying out their operations by increasing profitability and subsequently taking corrective actions so that BPD can carry out their function as an intermediary institution properly. This study aims to analyze the effect of (LDR), Non Performing Loan (NPL) and Profitability at PT BPD Bali. The data used in this study is secondary data, it is by looking from the monthly financial statements published by banking companies at PT. BPD Bali obtained from the Otoritas Jasa Keuangan (OJK) through the website www.ojk.go.id. This research used the method of determining the sample with the case study method based on monthly data from PT. BPD Bali 2017-2020 period. The analysis technique used is multiple linear regression analysis. The results showed that LDR had a positive effect on the profitability of PT. BPD Bali. NPL has a negative effect on the profitability of PT. BPD Bali. NIM has a positive effect on the profitability of PT. BPD Bali. The implication of this research is that company management should pay attention to LDR, NPL and NIM which is affect the profitability